Analisis dan Perancangan Ujian Terkomputerisasi Menggunakan Metode Linear Congruential Generator Untuk Pengacakan Soal (Studi Kasus: Sekolah Menengah Kejuruan Agathos) - Fernaldi Makmur; Benny Daniawan; Andri Wijaya (Komunitas Dosen Indonesia, 2019)
In this modern era, education begin to use more advanced technology in order to ease their activities such as semester exams. By taking advantage of computer technology in education will make semester exams become simpler during the process of the exam and scoring, as in shuffling the order of the question and scoring become faster and more accurate. Currently, Agathos Vocational High School still use manual exam system, and the process cost is high. They have to print out the test and answer paper, undisciplined students can cheating during exam, mistakes during marking the test, and unorganized archives when filing the student’s results. After finding out the current system in Agathos Vocational High School, To solving their current problems is develop a system that will organize the information electronically in filling the student’s grades and making a random order of questions, using Linear Congruential Generator (LCG) method. This computerized system will help the teachers to making the questions with inputting process, and will be done in three days, marking the answers and filling the grade are automatically done by system, then print it out to be Student’s Report. With using LCG method, can motivating the students to study as the order of the question is randomized by Student’s ID Number, the students will not be able to continue filling their answers after the time is up and this will reducing the possibility of cheating. The time needed to prepare exam questions was reduced from 8 days to 1 day. The system test results is 64% can be accepted by the user.